International market selection applied to a foreign direct investment of a SME - Weiß, Konstantin (2020)
The work project “International Market Selection Applied to a Foreign Direct Investment of a SME” seeks to find a solution to the organizational challenge of Boyens Backservice GmbH, a German SME, to identify, evaluate and select most preferable markets for a foreign direct investment. The method follows a three-step approach. First core markets are identified, which are then evaluated to the general FDI feasibility. This is concluded by an in-depth market analysis of the top two identified markets. The outcome yields the Czech market as the most preferable.